2022
DOI: 10.1080/22221751.2022.2063076
|View full text |Cite
|
Sign up to set email alerts
|

Novel H5N6 reassortants bearing the clade 2.3.4.4b HA gene of H5N8 virus have been detected in poultry and caused multiple human infections in China

Abstract: The globally circulating H5N8 avian influenza viruses bearing the clade 2.3.4.4b hemagglutinin (HA) gene are responsible for the loss of more than 33 million domestic poultry since January 2020. Moreover, the H5N8 viruses have reassorted with other avian influenza viruses and formed H5N1, H5N2, H5N3, H5N4, and H5N5 viruses in Europe, Africa, and North America. In this study, we analyzed 15 H5N6 viruses isolated from poultry and seven H5N6 viruses isolated from humans, and found these viruses formed seven diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 44 publications
(34 reference statements)
0
49
2
Order By: Relevance
“…Gu et al detected different genotypes of H5N6 viruses in China and found that the H5N6 viruses were reassortants that derived their HA genes from H5N8 viruses, NA genes from different duck H5N6 viruses, and certain internal genes from different low pathogenic viruses [ 15 ]. Most of the donor viruses of the NA and internal genes of the H5N6 viruses were previously detected in China, suggesting that the H5N6 reassortants were generated in ducks in China [ 15 ]. However, it seems that the four genotypes of the H5N1 viruses detected in China have not undergone any further reassortment in domestic birds in China.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gu et al detected different genotypes of H5N6 viruses in China and found that the H5N6 viruses were reassortants that derived their HA genes from H5N8 viruses, NA genes from different duck H5N6 viruses, and certain internal genes from different low pathogenic viruses [ 15 ]. Most of the donor viruses of the NA and internal genes of the H5N6 viruses were previously detected in China, suggesting that the H5N6 reassortants were generated in ducks in China [ 15 ]. However, it seems that the four genotypes of the H5N1 viruses detected in China have not undergone any further reassortment in domestic birds in China.…”
Section: Discussionmentioning
confidence: 99%
“…The H5 avian influenza viruses are becoming progressively more virulent in the mammalian mouse model. Some of the earliest H5N1 viruses could not replicate in mice [ 36 ], but more and more strains have now acquired this ability and some have become lethal in mice [ 4 , 10 , 15 ]. A series of amino acid substitutions in different proteins of avian influenza virus have been reported to increase its pathogenicity to mice [ 37–53 ], and many of these substitutions have been detected in the widely circulating H5N1 viruses, which explains why the H5N1 viruses we tested in this study were able to replicate in and kill mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All Astrakhan viruses in 2020 had 137A/158N/160A/186N residues in their HA proteins, which have been reported to increase the affinity to α-2,6 sialic acids. A recent study showed that new H5N6 reassortants bearing the HA gene of H5N8 virus clade 2.3.4.4b caused multiple human infections [24]. This virus generated in nature instead of a reverse genetically engineered virus in the laboratory demonstrated that both H5N8 and H5N6 viruses carrying the HA gene can mediate human infections.…”
Section: Discussionmentioning
confidence: 99%